Making sense of the public service mission in media: youth audiences, competition, and strategic management. Issue 1 (2nd January 2019) - Lowe, Gregory Ferrell; Maijanen, Päivi
ABSTRACT: Our study examines how the public service mission in media is being redefined as a strategic issue in legacy public broadcasting firms. Our research interest particularly focuses on the challenge of competition for youth audiences. The study investigates perceptions and responses among strategic managers ( N = 16). The authors use a blended framework of two theories: dominant logic and sense-making. Content analysis of interviews in Finland ( Yleisradio [Yle]), Germany ( Norddeutscher Rundfunk [NDR] and Radio Bremen [RB]), and Sweden ( Sveriges Television [SVT]) clarifies correspondence and contradictions among strategic managers of legacy mass media firms as they struggle to adapt their organisations to the demands of today's digital media environment. Findings indicate continuing commitment to legacy public service ideals that are perceived as beneficial but also pose complications in fulfilling the universal service mission's historic mission today. The dominant logic of heritage broadcasting is juxtaposed with the logic of digital communications in the management work required to balance countervailing pressures for change and continuity in pursuit of digital transformation.